Provisional Agenda for the Twenty-Fourth Meeting of the International Monetary and Financial Committee (IMFC). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Provisional Agenda 1. Adoption of Agenda-Opening Remarks by the Chair 2. The Managing Director's Consolidated Multilateral Surveillance Report - Presentation by the IMF Economic and Financial Counsellors The Managing Director's Action Plan - Presentation by the Managing Director 3. Approval of Press Communique.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Agenda; HQ1; IMF Governors Photograph; Meeting Hall; PP